James Whitcomb Riley papers - Riley, James Whitcomb, 1849-1916.
Correspondence and manuscripts and typescripts of poems. Includes a drawing by Riley of his friend Bill Nye. Correspondents include William C. Edgar, C. E. Farrell, Samuel E. Kiser, Clara E. Laughlin, James Newton Matthews, Cyrus F. McNutt, Dewitt Miller, James B. Pond, John Clark Ridpath, Louis Untermeyer, Eugene Fitch Ware, and others.
In part, typewritten transcript.
Author and poet, of Indianapolis, Ind. Also known as the "Hoosier poet."
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Edgar, William C. -- 1856-1932 -- Correspondence; Farrell, C. E. -- Correspondence; Kiser, Samuel E. -- 1862-1942 -- Correspondence; Laughlin, Clara E. -- 1873-1941 -- Correspondence; Matthews, James Newton, -- 1852-1910 -- Correspondence; McNutt, Cyrus F. -- Correspondence; Miller, Dewitt, -- 1857-1911 -- Correspondence; Nye, Bill, -- 1850-1896.; Pond, James B. -- 1838-1903 -- Correspondence; Ridpath, John Clark, -- 1840-1900 -- Correspondence; Untermeyer, Louis, -- 1885-1977 -- Correspondence; Ware, Eugene Fitch, -- 1841-1911 -- Correspondence; American poetry; Authors; Poets